Central nervous system involvement in T-cell lymphoma: A single center experience. (3rd May 2016) - Gurion, Ronit; Mehta, Neha; Migliacci, Jocelyn C; Zelenetz, Andrew; Moskowitz, Alison; Lunning, Matthew; Moskowitz, Craig; Hamlin, Paul; Horwitz, Steven
Abstract: Background We characterized the incidence of central nervous system (CNS) involvement, risk factors and outcome in a large single institution dataset of peripheral T-cell lymphoma (PTCL). Methods Retrospective review of the PTCL database at Memorial Sloan Kettering Cancer Center. We identified 231 patients with any subtype of PTCL between 1994–2011 with a minimum six months of follow-up or an event defined as relapse or death. Results Histologies included peripheral T-cell lymphoma–not otherwise specified (PTCL–NOS) (31.6%), angioimmunoblastic (16.9%), anaplastic large cell lymphoma (ALCL), ALK- (12.1%), ALCL, ALK + (6.1%), extranodal NK/T-cell lymphoma (7.4%), adult T-cell leukemia/lymphoma (ATLL) (7.4%), and transformed mycosis fungoides (8.7%). Seventeen patients had CNS disease (7%). Fifteen had CNS involvement with PTCL and two had diffuse large B-cell lymphoma and glioblastoma. Median time to CNS involvement was 3.44 months (0.16–103.1). CNS prophylaxis was given to 24 patients (primarily intrathecal methotrexate). Rates of CNS involvement were not different in patients who received prophylaxis. Univariate analysis identified stage III–IV, bone marrow involvement, >1 extranodal site and ATLL as risk factors for CNS disease. On multivariate analysis, >1 extranodal site and international prognostic index (IPI) ≥ 3 were predictive for CNS involvement. The median survival of patients with CNS involvement was 2.63 months (0.10–75). Conclusions Despite high relapse rates, PTCL, except ATLL, carries a low risk of CNS involvement. Prognosis with CNS involvement is poor and risk factors include: >1 extra nodal site and IPI ≥3.